Synergistic interactions between Candida albicans and Enterococcus faecalis promote toxin-dependent host cell damage - Mario Kapitan; Maria Joanna Niemiec; Nicolas Millet; Philipp Brandt; Md Estiak Khan Chowdhury; Anna Czapka; Ketema Abdissa; Franziska Hoffmann; Anna Lange; Mark Veleba; Sandor Nietzsche; Alexander S. Mosig; et al. (Proceedings of the National Academy of Sciences, 2025)
The fungus Candida albicans and the Gram-positive bacterium Enterococcus faecalis share mucosal niches in the human body. As opportunistic pathogens, both are found to expand population size during dysbiosis, and can cause severe systemic infections in susceptible individuals. Here, we show that the presence of C. albicans results in increased host cell damage by E. faecalis . Furthermore, E. faecalis aggravates oropharyngeal candidiasis in mice. Increased damage is mediated by enterococcal cytolysin, and involves both physical interaction and altered glucose availability. Physical interaction promotes accumulation of bacteria on host cells, facilitating contact of cytolysin with host cells. Glucose depletion by the metabolic activity of the fungus sensitized host cells to cytolysin. This work illustrates how a complex interplay between fungi and bacteria can result in detrimental consequences for the host.